Islamic Education and Digital Citizenship: Developing Ethical Muslim Learners in the Era of Social Media and Artificial Intelligence - Uria Hasnan (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2024)
This study investigates the role of Islamic education in developing digital citizenship competencies among Muslim students in an increasingly technology-driven society. The study employs a qualitative library research approach by systematically reviewing scholarly literature on digital citizenship, Islamic educational philosophy, artificial intelligence, and digital ethics. Data were analyzed using thematic content analysis to identify key pedagogical principles for cultivating responsible digital behavior. The findings indicate that Islamic education provides a strong ethical foundation for promoting digital responsibility through the values of amanah (trustworthiness), ṣidq (truthfulness), 'adl (justice), and iḥsān (excellence). Integrating these values into digital citizenship education enhances students' critical digital literacy, ethical online behavior, responsible social media engagement, and resilience against misinformation. The study proposes an Islamic Digital Citizenship Framework that combines technological competence with Qur'anic moral values to prepare ethically responsible Muslim citizens. The novelty of this study lies in integrating Islamic ethical principles with contemporary digital citizenship competencies within a comprehensive educational framework suitable for the age of artificial intelligence